Small firm formation and regional economic development / edited by Michael W. Danson - "Danson , Michael W. (ed.)" (London, 1996)
Drawing on studies and expertise from around the world, this book describes the transition from research to policy and covers the pre-requisites to successful new firm formation policies. At a time when a new firm formation is promoted by central and local government, business development agencies and the private sector, this book questions the economic dependence on small firms and explores the relevance of networking, information and advice.
Keywords: Small business enterprises